Market Basket Analysis Using Apriori Algorithm to Find Effective Fiscal Policy Mix with R Programming - Isnen Hadi Al Ghozali; Arief Wibowo (Decode: Jurnal Pendidikan Teknologi Informasi, 2023)
Fiscal policy drives a country's economy and is the most effectivepolicy to restore a country's economy. When a recession occurs, the fiscal policy helps a country increase aggregate demand in the market for goods and services. This study proposes a fiscal policy mix that can be implemented based on historical data. So this research focuses on  using  association rules to assist decision-makers (regulators in  adopting  appropriate  fiscal  policies  in  the global VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. Therefore, an experimental research approach was used in this study to produce the best association rules. The research was carried out in six stages to obtain conclusions, namely problem identification in the research sample and literature review related to apriori algorithms, data collection, data pre-processing, parameter determination, research findings building a priori algorithms, and knowledge extraction formed from a priori algorithms. Based on the experimental results using the a priori algorithm, 657 rules were obtained with a minimum variation of two to six itemsets. Rule 6 produces an average value of the budget performance of 90.65. Rule 6 also says that the performance value of the budget can  be  increased  by  spreading  out  funding  sources  and  ensuring  that  operational  spending  is  as  efficient  as possible.